2014
DOI: 10.1016/j.jhep.2013.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious effect of oltipraz on extrahepatic cholestasis in bile duct-ligated mice

Abstract: Background & Aims Oltipraz (4-methyl-5(pyrazinyl-2)-1-2-dithiole-3-thione), a promising cancer preventive agent, has an anti-oxidative activity and ability to enhance glutathione biosynthesis, phase II detoxification enzymes and multidrug resistance-associated protein-mediated efflux transporters. Oltipraz can protect against hepatotoxicity caused by carbon tetrachloride, acetaminophen and alpha-naphthylisothiocyanate. Whether oltipraz has hepato-protective effects on obstructive cholestasis is unknown. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 43 publications
3
33
0
Order By: Relevance
“…Recent works support the crucial role of the analysis of the MMPs activation not only after 1-2 weeks after BDL but also after few days of occlusion [36, 37]. We confirm in rats the previous results in mice because we also observed an increase in MMP-2 and MMP-9 that in our conditions occurs significantly in RL than in ML and LL.…”
Section: Discussionsupporting
confidence: 92%
“…Recent works support the crucial role of the analysis of the MMPs activation not only after 1-2 weeks after BDL but also after few days of occlusion [36, 37]. We confirm in rats the previous results in mice because we also observed an increase in MMP-2 and MMP-9 that in our conditions occurs significantly in RL than in ML and LL.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, recent studies have shown that the NRF2 activators such as UDCA and oltipraz induced MRP efflux transporters in rodent liver (Eba et al, 2013;Okada et al, 2008;Weerachayaphorn et al, 2014), and NRF2 binds to AREs at -9919 bp in the mouse MRP3 gene and to AREs/antioxidant response-like elements a t -3753 to -3767 bp in the mouse MRP4 gene (Maher et al, 2007). In this study, BDL caused intrinsic activation of NRF2 in mice as an adaptive response, however, this adaption was not potent in fully preventing cholestatic liver injury as demonstrated by marked liver pathological alteration and upregulation of multiple serum and liver biochemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Here, a reduction of obesity and hepatic lipids and an improvement of glucose tolerance were observed in rodent models [68]. However, these molecules are associated with toxic effects, which could have been a considerable confounding factor in the metabolic studies [9, 10]. Genetic models leading to either a loss-of- or gain-of-Nrf2 function gave no clear picture about the role of Nrf2 in hepatic lipid and carbohydrate metabolism [1120].…”
Section: Introductionmentioning
confidence: 99%